Boehmite@SiO2@ Tris (hydroxymethyl)aminomethane‐Cu(I): a novel, highly efficient and reusable nanocatalyst for the C‐C bond formation and the synthesis of 5‐substituted 1H‐tetrazoles in green media. (9th July 2020) - Ghorbani‐Choghamarani, Arash; Aghavandi, Hamid; Mohammadi, Masoud
Abstract : In this work, a versatile protocol was introduced for the preparation of a new Cu(I) supported complex on Silica supported boehmite nanoparticles (Boehmite@SiO2 @Tris‐Cu(I)). The structure of the catalyst was comprehensively characterized using Fourier transform infrared spectroscopy (FT‐IR), X‐Ray Diffractometer (XRD), energy‐dispersive X‐ray spectroscopy (EDS), inductively coupled plasma atomic emission spectroscopy (ICP), X‐ray mapping, thermogravimetric analysis (TGA) and scanning electron microscopy (SEM) techniques. The catalytic activity of this catalyst was studied in the Suzuki cross‐coupling reaction and synthesis of 5‐substituted 1H‐tetrazole derivatives in ethanol and PEG‐400 respectively as green solvents. In this sense, simple preparation of the catalyst from the commercially available materials, high catalytic activity, simple operation, short reaction times, high yields and use of green solvent are some advantages of this protocol. Finally, it is worth mentioning that this nanocatalyst was easily recovered, and reused for several times without significant loss of its catalytic efficiency. In addition, stability of the catalyst after recycling was confirmed by FT‐IR technique. Abstract : Boehmite@SiO2 @tris (hydroxymethyl)aminomethane‐Cu(I) was prepared, characterized and applied for the C‐C bond formation and synthesis of 5‐substituted 1H‐tetrazoles in green media.